2020
DOI: 10.3233/hsm-190734
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dissatisfaction on funders’ decision to reinvest in crowdfunding: A distrust-based perspective

Abstract: BACKGROUND: In recent years, crowdfunding platforms have gained importance in the financing industry. An emerging issue is that only a fraction of investors decide to reinvest after the initial investment experience. One key factor that might be responsible for low reinvest rates, which ultimately results in lower crowdfunding success and unsustainable crowdfunding platforms, is dissatisfaction. OBJECTIVE: This paper aims to shed light on the repercussions of dissatisfying investment experiences. First, the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…business) uncertainty on backers' satisfaction. Gierczak et al (2015) discussed the possible delay of rewards and its influence on backers' satisfaction, and Strohmaier et al (2020) studied the role of backers' dissatisfaction in dictating future investment decisions. Finally, Zhao et al (2019) showed that psychological contract violation, a manifestation of backers' negative emotions resulting from a contract breach, is negatively associated with backers' funding intentions.…”
Section: Crowdfunding In Times Of Crisismentioning
confidence: 99%
“…business) uncertainty on backers' satisfaction. Gierczak et al (2015) discussed the possible delay of rewards and its influence on backers' satisfaction, and Strohmaier et al (2020) studied the role of backers' dissatisfaction in dictating future investment decisions. Finally, Zhao et al (2019) showed that psychological contract violation, a manifestation of backers' negative emotions resulting from a contract breach, is negatively associated with backers' funding intentions.…”
Section: Crowdfunding In Times Of Crisismentioning
confidence: 99%